Trastuzumab deruxtecan (DS-8201a) in patients with advanced HER2-positive breast cancer previously treated with trastuzumab emtansine: a dose-expansion, phase 1 study. Issue 6 (June 2019) - Tamura, Kenji; Tsurutani, Junji; Takahashi, Shunji; Iwata, Hiroji; Krop, Ian E; Redfern, Charles; Sagara, Yasuaki; Doi, Toshihiko; Park, Haeseong; Murthy, Rashmi K; Redman, Rebecca A; Jikoh, Takahiro; et al.
Summary: Background: Trastuzumab deruxtecan (DS-8201a) is a novel HER2-targeted antibody–drug conjugate with a humanised anti-HER2 antibody, cleavable peptide-based linker, and potent topoisomerase I inhibitor payload. A phase 1, non-randomised, open-label, multiple-dose study was done to assess the safety, tolerability, and activity of trastuzumab deruxtecan in HER2-expressing, advanced solid tumours. The dose escalation (part 1) has previously been reported and the recommended doses for expansion of 5·4 mg/kg or 6·4 mg/kg were established. In this Article, we report the safety and preliminary activity results from this phase 1 trial in all patients with HER2-positive advanced-stage breast cancer with previous trastuzumab emtansine treatment who received trastuzumab deruxtecan at the recommended doses for expansion. Methods: We did an open-label, dose-escalation and dose-expansion phase 1 trial at eight hospitals and clinics in the USA and six in Japan. Eligible patients were at least 18 years old in the USA and at least 20 years of age in Japan and had advanced solid tumours (regardless of HER2 expression in dose escalation or HER2 expression or mutation in dose expansion). The recommended doses for expansion of 5·4 mg/kg or 6·4 mg/kg trastuzumab deruxtecan were administered intravenously to patients once every 3 weeks until withdrawal of consent, unacceptable toxicity, or progressive disease. In this Article, all patients with HER2-positive advanced-stage breast cancer with previous trastuzumab emtansine treatment who received trastuzumab deruxtecan at the recommended doses for expansion were analysed together. The primary endpoints of the study were safety and preliminary activity (proportion of patients who achieved an objective response as assessed by the investigators). The activity evaluable set included all patients who received at least one dose of trastuzumab deruxtecan at the recommended doses for expansion, and for whom both baseline and post-treatment activity data were available. The safety analysis set included all patients who received at least one dose of trastuzumab deruxtecan at the recommended doses for expansion. Enrolment for patients with HER2-positive breast cancer has been completed. This trial is registered atClinicalTrials.gov, numberNCT02564900, and ClinicalTrials.jp, number JapicCTI-152978. Findings: Between Aug 28, 2015, and Aug 10, 2018, 115 of 118 patients with HER2-positive breast cancer were treated with at least one dose of trastuzumab deruxtecan at the recommended doses for expansion. All patients had at least one treatment-emergent adverse event. Frequent grade 3 or worse treatment-emergent adverse events included anaemia (19 [17%] of 115) and decreased neutrophil (16 [14%]), white blood cell (ten [9%]), and platelet (nine [8%]) counts. At least one serious treatment-emergent adverse event occurred for 22 (19%) patients. Investigators reported 20 cases of interstitial lung disease, pneumonitis, or organising pneumonia, including one grade 3 event and two treatment-related deaths due to pneumonitis. One death unrelated to study treatment was due to progressive disease. 66 (59·5%; 95% CI 49·7–68·7) of 111 patients had a confirmed objective response. Interpretation: Trastuzumab deruxtecan had a manageable safety profile and showed preliminary activity in trastuzumab emtansine-pretreated patients with HER2-positive breast cancer. These results suggest that further development in phase 2 and 3 clinical trials for HER2-positive breast cancer is warranted. Funding: Daiichi Sankyo Co, Ltd.